2023
DOI: 10.1111/gcbb.13099
|View full text |Cite
|
Sign up to set email alerts
|

Integrating perennial biomass crops into crop rotations: How to remove miscanthus and switchgrass without glyphosate

Eva Lewin,
Andreas Kiesel,
Elena Magenau
et al.

Abstract: Perennial energy grasses have gained attention in recent years as a promising resource for the bioeconomy because of their benign environmental profile, high stress tolerance, high biomass yields and low input requirements. Currently, strong breeding efforts are being made to extend the range of commercially available miscanthus and switchgrass genotypes. In order to foster farmers' acceptance of these crops, and especially of novel hybrids, more information is required about how they can be efficiently integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Nevertheless, the use of chemical herbicides such as glyphosate is of concern; therefore, alternatives should be found for the eradication of perennial biomass crops under ecological and sustainable criteria. As a recent study demonstrated, a perennial Miscanthus stand could be eradicated by a combination of tillage and grass herbicides from maize cultivation and subsequent cultivation of maize and winter wheat [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of chemical herbicides such as glyphosate is of concern; therefore, alternatives should be found for the eradication of perennial biomass crops under ecological and sustainable criteria. As a recent study demonstrated, a perennial Miscanthus stand could be eradicated by a combination of tillage and grass herbicides from maize cultivation and subsequent cultivation of maize and winter wheat [30].…”
Section: Introductionmentioning
confidence: 99%